PROSES KOMUNIKASI ORANG TUA DAN ANAK DALAM KEPUTUSAN PROGRAM STUDI DI PERGURUAN TINGGI - Zakira, Tuhfah; Nur Suryanto Gono, Joyo; Manalu, S. Rouli (Interaksi Online, 2024)
This research aims to understand the communication process between parents and children in making decisions regarding the choice of a study program in higher education. In the family context, educational decisions often involve complex discussions between parents and children, where topics like the child's interests, career aspirations, and future become key points of discussion. This study uses an Interpretative Phenomenological Analysis (IPA) approach to explore the subjective experiences of children and parents during this communication process. Data were collected through in-depth interviews with four parent-child pairs who are currently or have already gone through the process of selecting a study program in higher education. The research findings indicate that the communication style of parents, such as authoritative or democratic styles, has a significant impact on the final decision. Moreover, factors such as parental expectations, the child's interests, as well as social and cultural pressures also influence the dynamics of communication. Children involved in open communication with their parents are more likely to choose study programs that align with their own interests, while in cases of authoritarian communication, the decision is more often determined by the parents. These findings emphasize the importance of openness and support in the educational decision-making process within the family environment. This research also offers practical implications for families and educational institutions in improving more effective and supportive communication between parents and children.